2014
DOI: 10.4028/www.scientific.net/amr.1013.194
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Wear-Resistant Weld Deposit Formed on Martensitic Steel Using the Electric-Arc Method

Abstract: Studies on the structure and the phase composition of the deposited material were carried out using methods of X-ray structure analysis and electron diffraction microscopy of extract coal replicas and thin foils on steel Hardox 400. Formation of a multiphase state, represented by grains of α-iron and inclusions of carbide phases based on iron, chromium, and niobium, is revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In addition, combined with the results reported in references [9][10][11], it is sure that the presence of a large number of bend extinction contours indicating the bend-torsion of carbide phase crystal lattice, as the dark field image of iron carbide structure shown in Fig. 3b.…”
Section: Figure 2 Tem Image Of the Carbide Phase In The Surfacing Trmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, combined with the results reported in references [9][10][11], it is sure that the presence of a large number of bend extinction contours indicating the bend-torsion of carbide phase crystal lattice, as the dark field image of iron carbide structure shown in Fig. 3b.…”
Section: Figure 2 Tem Image Of the Carbide Phase In The Surfacing Trmentioning
confidence: 78%
“…As that proposed in our previous works [3,4,10], the thin foils prepared from the surface layer of the coatings irradiated by pulse electron beams with the above mentioned parameters was investigated by TEM with the carbon replica technique. It was found that the submicro-nanocrystal multiphase structure with cellular and dendritic crystallization of submicron sizes (200-500 nm) is formed in the surface layer, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High hardness Hardox 450 steel is obtained by quenching a sheet with special composition to generate martensite structure. To improve its technological properties further, the steel underwent additional modification including surface processing for obtaining the demanded properties [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…High hardness Hardox 450 steel is obtained by quenching a sheet with special composition to generate martensite structure. To improve its technological properties further, the steel underwent additional modification including surface processing for obtaining the demanded properties [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%